Construction of Vicinal Tetrasubstituted Stereogenic Centers via a Mannich‐Type Organocatalyzed Addition of Δ2‐Pyrrolin‐4‐ones to Isatin Imines. Issue 6 (15th January 2018) - Ričko, Sebastijan; Meden, Anže; Ciber, Luka; Štefane, Bogdan; Požgan, Franc; Svete, Jurij; Grošelj, Uroš
Abstract: Racemic Δ 2 ‐pyrrolin‐4‐ones ( i. e . 4‐pyrrolones), easily available in two steps from N ‐protected α ‐amino acids, undergo organocatalysed asymmetric Mannich‐type addition to isatin‐derived ketimines to furnish the non‐racemic oxindole‐Δ 2 ‐pyrrolin‐4‐one adducts, stereoselectively (up to 96% ee, dr ≥15:1). The oxindole–pyrrolone products feature vicinal tetrasubstituted carbon stereocenters. The developed protocol has a broad substrate scope and tolerates diverse substituents at position C‐5 in 4‐pyrrolones and at positions N‐1 and C‐5/7 in isatin imines. Abstract :